Anaesthetic Management of a Patient with Brugada Pattern Undergoing Surgery for Cellulitis - Dr Shaheen Khan M, Balasubramaniam Gayathri, Dr Aravindhan K Y, Sai Hrudaya Harshitha Akondi (South Eastern European Journal of Public Health, 2025)
Brugada syndrome is a genetic condition that has no connection to structural cardiac disease, characterised by an ECG pattern revealing the right bundle branch block, persistent ST-segment elevation in the right precordial leads (V1-V3), and a propensity for malignant. We successfully managed a 60-year-old asymptomatic male patient with Brugada syndrome, identified during pre-anaesthesia evaluation. The patient had a history of early abrupt cardiac death in his family, and his electrocardiogram revealed a Brugada pattern. He was posted for split-thickness skin graft (SSG) under general anaesthesia, following wound debridement for right leg cellulitis. The intraoperative course was uneventful, with the patient remaining haemodynamically stable throughout. The postoperative period was also uneventful. Consequently, early diagnosis and appropriate anaesthetic management require a complete patient history, careful assessment of test data, and ECG.